Stimulus-specific gene expression profiles associated with grooming behavior and Varroa destructor resistance in honey bees - Russo, Romina M.; Pietronave, Hernán; Conte, Claudia A.; Liendo, María C.; Basilio, Alicia; Lanzavecchia, Silvia B.; Scannapieco, Alejandra C. (Frontiers in Bee Science, 2024)
Grooming behavior is one of the mechanisms of social immunity in Apis mellifera. This behavior has been proposed as an active strategy of honey bees to restrain the population growth of the ectoparasitic mite Varroa destructor in honey bee colonies.The characterization of honey bee stocks with high grooming behavior is of utmost importance for honey bee breeding programs to set the background for mite resistance biomarker-based selection. In this study, we analyzed the expression level of 11 candidate genes putatively involved in grooming and hygiene behaviors in adult workers from mite-resistant (R) and mite-susceptible (S) honey bee stocks. Heads and bodies of worker bees from both stocks, previously tested for grooming response to two treatments (mite infestation and a paintbrush touch control stimulus) were assessed by qPCR. In the head, R bees exposed to mite infestation showed higher levels of Nrx1 and Dop2 and lower levels of Obp3 than S bees. At the body level, R and S bees differed in the expression levels of Nrx1, Oa1, Obp4, Obp14, Obp16, Obp18, Spf45, CYP9Q3, with no stimulus-specific pattern. Overall, our results suggest the involvement of some of the analyzed genes in the specific response to mite infestation, possibly related to the sensitivity and specificity of the R bee to this stimulus at the head level, while other genes would be involved in the non-specific motor response to irritants at the body level. The present study provides new insights into the characterization of the grooming behavior in a selected honey bee stock and increases the available information on its underlying molecular mechanisms. We discuss the putative functions and use of the assessed genes as potential tools for biomarker-assisted selection and improvement of Varroa mite control strategies in honey bee colonies.